Reintroduction and monitoring of the bird Amazona aestiva (Psittaciformes: Psittacidae) in Brazil - Fraga, Ricardo Evangelista (2023)
Introduction: Reintroduction is a procedure used to reestablish wild animal populations. Objective: The present study aimed to evaluate the success of reintroducing Amazona aestiva and investigate whether abiotic factors (temperature, humidily, and luminosity) interfere with the search for food supplementation in feeders installed in the release area. Methods: Pre-release evaluations were initiated with 59 Amazonas spp. Tests were run to stool parasitological tests, leukocytes, flight capacity, and level of animal-human interaction. In all, 33 animals were selected and sent to the release area, which is an ecotone between the Atlantic Forest and the Caatinga biomes. After release, visits to the feeders and survival in the area were monitored for a year. Abiotic factors were also recorded in these periods. Results: The stool parasitological tests revealed the presence of Heterakis spp. and Eimeira spp. The leukocyte parameters were within the reference values for the species. At least 50% of the released animals survived after one year, with recordings of reproductive events. Abiotic factors did not interfere with the animal visits to the feeder. However, the variable humidity best explained visits in the morning, while the variables temperature and luminosity most influenced visits in the afternoon. Conclusion: The reintroduction observed and presented here is on the threshold of the classification as successful. The installed feeders and artificial nests caused the animals to stay in the area for monitoring. Abiotic factors may influence daily behavioral decision-making related to the use of supplementary feeding in reintroduced parrots.